Negro Employment in the Aircraft Industry - Weaver, Robert C. (Quarterly Journal of Economics, 1945)
Introduction: early opposition, 597. — Impediments to Negro employment: employer attitudes, 600; union attitudes, 605. — Methods of introducing Negro labor: Lockheed-Vega, 608; North American, 610; Wright Aeronautical, 611. — Labor utilization: over-all increase in Negro workers, 613; particular labor markets, 615. — The rôle of labor unions, 621. — Conclusion, 623.